2017
DOI: 10.12700/aph.14.8.2017.8.6
|View full text |Cite
|
Sign up to set email alerts
|

The X and Y Generations’ Characteristics Comparison

Abstract: The aim of this paper is to identify generational differences, also similarities among university students in order to realise the reason of generational gap. Data for this study were collected through survey analysis (n=783). Findings indicated significant differences among X and Y generations usage of new technological innovation (i.e. also applications and devices). While Generation Y members (Millennials) are technology and social media addicted, the members of elder generation are in a different life peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…In line with our findings on communication channels, past studies found that younger individuals use mobile phones more frequently to communicate with friends compared to older people [Forgays et al, 2014]. A higher affinity for innovative payment technologies may be the reasoning for younger consumers to prefer online payment instruments, as this cohort of consumers grew up with the internet and evolving innovative payment methods [Kolnhofer-Derecskei et al, 2017]. Similarly, a qualitative study investigating communication preferences of older adults (older than 66 years) via semi-structured interviews revealed stronger preferences for in-person and written communication rather than technologically mediated communication [Yuan et al, 2016].…”
Section: Discussionsupporting
confidence: 88%
“…In line with our findings on communication channels, past studies found that younger individuals use mobile phones more frequently to communicate with friends compared to older people [Forgays et al, 2014]. A higher affinity for innovative payment technologies may be the reasoning for younger consumers to prefer online payment instruments, as this cohort of consumers grew up with the internet and evolving innovative payment methods [Kolnhofer-Derecskei et al, 2017]. Similarly, a qualitative study investigating communication preferences of older adults (older than 66 years) via semi-structured interviews revealed stronger preferences for in-person and written communication rather than technologically mediated communication [Yuan et al, 2016].…”
Section: Discussionsupporting
confidence: 88%
“…, 2018). The psychological factors refer to numerous individual attributes such as personality characteristics, self-confidence, self-consciousness, risk tolerance, personal preferences, motivations and attitudes (Kolnhofer-Derecskei et al. , 2017; Rusu et al.…”
Section: General Backgroundmentioning
confidence: 99%
“…Technological growth was explicitly apparent in various industries, the labour market and the educational sector. The rise of high-tech has also had a great impact on the daily lives of people, which in turn caused substantial changes in individuals' mindsets and their psychological attributes (Kolnhofer-Derecskei et al, 2017). Globalisation processes begun in the early 2000s have similarly had significant repercussions which are burgeoning still.…”
Section: Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keeping both points of view in mind, different classifications can be found captured in an assortment of proposals [5,[12][13][14], without, in a lot of cases, reaching agreement (Table 1). The cutoff points or limits that different works establish to classify generations are not always exact, but they must be used as a tool with the aim of analyzing different elements and, by doing so, designing successful solutions that can fulfill generational needs.…”
Section: Introductionmentioning
confidence: 99%